Composite material for concrete reinforcement, concrete reinforcing bars, and method for manufacturing composite material for concrete reinforcement

JP7936551B2Active Publication Date: 2026-10-16KANAZAWA INSTITUTE OF TECHNOLOGY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021172774
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-22
Publication Date
2026-10-16
Estimated Expiration
2041-10-22

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、耐アルカリ性およびハンドリング性が良好な熱可塑性樹脂を含浸させたコンクリート補強用複合材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936551000002
    Figure 0007936551000002
  • Figure 0007936551000003
    Figure 0007936551000003
  • Figure 0007936551000004
    Figure 0007936551000004
Patent Text Reader

Abstract

To provide a novel concrete reinforcement composite material that is inexpensive and is easy in its secondary processing.SOLUTION: In a concrete reinforcement composite material 10, a core material 12 is formed from a fiber bundle of reinforced fibers. A coating layer 14 of thermoplastic resin coats the core material 12. The core material 12 is impregnated with the thermoplastic resin, the thickness of the coating layer 14 is 85 μm or more, and the fiber volume content Vf of the core material 12 is 60% or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a composite material for concrete reinforcement and concrete reinforcing bars. [Background technology]

[0002] Reinforced concrete structures are susceptible to corrosion from moisture and salt due to the reinforcing steel used, leading to deterioration over time. Therefore, to extend the lifespan of concrete structures, the use of composite materials such as fiber-reinforced plastics (FRP) as a substitute for reinforcing steel has been proposed. For example, Patent Document 1 describes a concrete reinforcing material using thermosetting resin. In the manufacture of the concrete reinforcing material described in Patent Document 1, it takes time for the thermosetting resin to harden through a heat-induced curing reaction after impregnation of the reinforcing fibers, resulting in low production efficiency and high manufacturing costs. Furthermore, once thermosetting resin hardens, it cannot be softened by heating, making secondary processing such as bending impossible. For this reason, concrete reinforcing materials impregnated with thermoplastic resin instead of thermosetting resin have been devised. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 11-124957 [Overview of the project] [Problems that the invention aims to solve]

[0004] In concrete reinforcing materials impregnated with thermoplastic resin, there is room for improvement in alkali resistance and handling properties.

[0005] Therefore, an object of the present invention is to provide a composite material for concrete reinforcement impregnated with a thermoplastic resin that has good alkali resistance and handling properties. [Means for solving the problem]

[0006] One aspect of the present invention is a composite material for concrete reinforcement. This composite material for concrete reinforcement comprises a core material formed from a fiber bundle of reinforcing fibers and a coating layer of thermoplastic resin covering the core material, wherein the thermoplastic resin is impregnated into the core material, the thickness of the coating layer is 85 μm or more, and the fiber volume content Vf of the core material is 60% or more.

[0007] Another aspect of the present invention is concrete reinforcement bars. These concrete reinforcement bars include the above-mentioned composite materials for concrete reinforcement. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide a composite material for concrete reinforcement that is impregnated with a thermoplastic resin with good alkali resistance and handling properties. [Brief explanation of the drawing]

[0009] [Figure 1] This is a cross-sectional view of a concrete reinforcement composite material according to an embodiment. [Figure 2] This is a cross-sectional view of the longitudinal section of a concrete reinforcement composite material according to an embodiment. [Figure 3] This is a schematic diagram showing a manufacturing apparatus for concrete reinforcement composite materials according to an embodiment. [Figure 4] This diagram illustrates the pickup machine shown in Figure 3. [Figure 5] This diagram illustrates the angle of the roller shown in Figure 4. [Figure 6] These are X-ray CT images of the FRP rods of Examples 1 and 2, and Comparative Examples 1 and 2. [Figure 7] This graph shows the relationship between the twist angle and the distance from the center for Examples 3-7. [Figure 8] These are photographs showing BFPP bent at 90 degrees and 180 degrees. [Modes for carrying out the invention]

[0010] Hereinafter, embodiments for implementing the present disclosure will be described in detail with reference to the drawings and the like. The embodiments are illustrative rather than limiting the invention, and all features and combinations thereof described in the embodiments are not necessarily essential to the nature of the invention.

[0011] (Composite material for concrete reinforcement) Figure 1 is a cross-sectional view of the transverse section of the composite material for concrete reinforcement according to the embodiment. Figure 2 is a cross-sectional view of the longitudinal section of the composite material for concrete reinforcement according to the embodiment. The composite material for concrete reinforcement (hereinafter also simply referred to as composite material) 10 shown in Figure 1 and Figure 2 includes a core material 12 formed from a fiber bundle of reinforcing fibers, and a thermoplastic resin coating layer 14 that covers the core material 12.

[0012] The core material 12 is impregnated with a thermoplastic resin, the thickness of the coating layer 14 is 85 μm or more, and the fiber volume content V of the core material 12 f is 60% or more. The core material 12 is impregnated with a thermoplastic resin, and the thickness of the coating layer and V f are within such ranges, whereby it is possible to provide a composite material for concrete reinforcement that has high alkali resistance, high strength, high flexibility, and enables secondary processing such as bending. Here, the thickness of the coating layer 14 is the thickness of the coating layer measured at 20 points, and all the measured values are within the range of 85 μm or more. The fiber volume content V of the core material f is the volume ratio of the reinforcing fibers to the core material calculated from an X-ray CT photograph of the transverse section of the composite material.

[0013] From the viewpoint of further improving alkali resistance and strength, the thickness of the coating layer 14 is preferably 250 μm or more, more preferably 320 μm or more.

[0014] It is preferable that the non-circularity of the composite material 10 for concrete reinforcement is 1 to 5%, and the non-circularity of the core material 12 is 1 to 6%. When the non-circularity of the composite material 10 for concrete reinforcement and the non-circularity of the core material 12 are each within the above ranges, the moldability of the composite material can be improved. Specifically, when these non-circularities are each within the above ranges, the cross-section of the coating layer has a uniform thickness, which makes fibers less likely to protrude from the surface and suppresses fuzzing. The suppression of fuzzing inhibits contact between the die and the fibers in the pultrusion step after impregnation. For this reason, fiber breakage can be suppressed, that is, moldability can be improved.

[0015] The lower the non-circularity, the closer the cross-sectional shape of the composite material is to a perfect circle. Here, "non-circularity" is calculated by the following formula. Non-circularity (%) = (a-b) / c × 100 (1) In the formula, a represents the average value of the major axes of the cross-sections at 5 positions, b represents the average value of the minor axes of the cross-sections at 5 positions, and c represents the average value of the average diameters of the cross-sections at 5 positions. Specifically, a, b and c are calculated from the X-ray CT photograph of the cross-section as follows. For one cross-section, each of the major axis and the minor axis is measured 3 times (N=3), and the respective average values are calculated. Further, the average value of all the measured major axes and minor axes (9 measured values) is calculated as the average diameter. The major axis, minor axis and average diameter of the 5 cross-sections are each averaged to be a, b and c in the formula (1). The non-circularity of the composite material for concrete reinforcement is calculated from X-ray CT photographs of 5 cross-sections including both the core material and the coating layer of this composite material. The non-circularity of the core material is calculated from 5 cross-sections of the core material excluding the coating layer in the X-ray CT photograph of the cross-section of the composite material.

[0016] It is preferable that the twist angle of the reinforcing fibers contained in the core material 12 is 0.087 to 15°. If the twist angle is within this range, the moldability of the composite material can be improved. Specifically, the twist of the reinforcing fibers causes the fibers to move towards the center during the pultrusion process. Therefore, contact between the die and the fibers is suppressed during the pultrusion process. This suppresses fiber breakage, and thus improves moldability. Here, "twist angle" refers to the average value of the twist angles of the fibers measured at three points from a point close to the center of the longitudinal cross-section of the composite material (the center of the core material) to a point close to the coating layer. If the diameter of the composite material is small (for example), the twist angle is measured at intervals of 0.25 mm from the center, and the average value of three points is calculated at each distance. If the diameter of the composite material is large, the twist angle is measured at intervals of 0.5 mm from the center, and the average value of three points is calculated at each distance. It is preferable that all twist angles measured at equal intervals from the center to a point close to the coating layer are within the above range.

[0017] It is preferable that the twist angle of the reinforcing fibers is proportional to the distance from the center of the core material. This improves the moldability and handling properties of the composite material.

[0018] The thermoplastic resin is preferably a polyolefin resin. This allows for the provision of a composite material that is inexpensive, has excellent chemical and water resistance, and is easy to process, such as bending. Examples of polyolefin resins include polyethylene and polypropylene. Polypropylene is preferred because it is less expensive.

[0019] The reinforcing fibers forming the core material 12 are preferably at least one selected from the group consisting of glass fibers, basalt fibers, carbon fibers, and aramid fibers.

[0020] The fiber diameter, fineness, and number of reinforcing fibers can be adjusted according to the size of the desired composite material. For example, the fiber diameter may be 7 to 19 μm. For example, the fineness may be 2400 to 24000 tex. For example, the number of fibers may be 8000 to 120000.

[0021] (Method for manufacturing composite materials for concrete reinforcement) The following describes a method for manufacturing a concrete reinforcement composite material according to an embodiment. The concrete reinforcement composite material according to the embodiment can be manufactured by pultrusion molding. Figure 3 is a schematic diagram showing a manufacturing apparatus for the concrete reinforcement composite material according to the embodiment. The manufacturing apparatus 100 shown in Figure 3 includes a roving heater 102, an impregnation head 104, an extruder 106, a die 108, a cooling device 110, and a take-up machine 112.

[0022] As shown in Figure 1, the fiber bundles (roving bundles) 114 of reinforcing fibers (roving) are led to a roving heater 102 for preheating. Downstream of the roving heater 102 is an impregnation head 104 and an extruder 106 equipped with a screw 116. Molten thermoplastic resin (molten resin) 118 is continuously supplied to the impregnation head 104 from the extruder 106. A die 108 is attached to the outlet of the impregnation head 104. The die 108 shapes the concrete reinforcement composite material 120 formed from the twisted, high-temperature resin-impregnated fiber bundles taken from the impregnation head 104.

[0023] Downstream of the impregnation head 104, a cooling device 110 is provided to cool the high-temperature composite material 120 from the impregnation head 11 in cooling water. Downstream of the cooling device 110, a take-up machine 112 is provided, which is equipped with a pair of rollers 122 and 124. The take-up machine 112 twists the resin-impregnated fiber bundles with the rollers 122 and 124 and takes up the composite material 120 from the upstream side.

[0024] Figure 4 is a diagram illustrating the take-up machine in Figure 1. Figure 5 is a diagram illustrating the roller angles shown in Figure 2. The take-up machine 15 includes a pair of rollers 122 and 124 that are positioned opposite each other, with their respective rotation axes held on parallel planes (horizontal planes) and their rotation axes intersecting, so as to sandwich the composite material 120 from the upstream side. In Figure 2, the rotation axis of the upper roller 122 and the rotation axis of the lower roller 124 are not perpendicular to the take-up direction (travel direction) of the composite material 120, but are set in directions opposite to each other with respect to the take-up direction in a plan view, and are offset by a predetermined angle at the same angle.

[0025] As shown in Figure 5, in a plan view, the angle between the line perpendicular to the rotation axis a of the roller 122 (124) and the pull direction (travel direction) of the composite material 120 is defined as the roller angle 2θ. The metal rollers 122 and 124 have minute irregularities formed by knurling across their entire surface (outer surface of the roller).

[0026] In the manufacturing apparatus 100 configured in this way, first, the fiber bundle 114 is heated by the roving heater 102 and guided into the impregnation head 104. The fiber bundle 114 is impregnated with resin in the impregnation head 104, which is filled with high-temperature molten resin 118 supplied from the extruder 106, and resin-impregnated fiber bundles are formed. These resin-impregnated fiber bundles are twisted by the twisting action of rollers 122 and 124, and twist is generated and grows within the impregnation head 104. In this way, the fiber bundle 114 is impregnated with molten resin 118 supplied from the extruder 106, and twist is given to the resin-impregnated fiber bundles, and the composite material 120 formed from the twisted resin-impregnated fiber bundles is continuously drawn from the impregnation head 104.

[0027] The high-temperature composite material 120, continuously drawn from the impregnation head 104 through the die 108, is cooled and hardened by the cooling device 110 and then guided to the rollers 122 and 124. The composite material 120 cooled by the cooling device 110 is subjected to twisting and drawing by the rollers 122 and 124, which are set to a predetermined twisting angle θ. In this way, the concrete reinforcement composite material according to the embodiment can be obtained.

[0028] (Concrete reinforcement bars) The concrete reinforcing bar according to this embodiment includes the above-mentioned composite material for concrete reinforcement. For example, concrete reinforcing bars can be obtained by using the composite material as strands, bundling several of them together, or twisting them to increase their diameter to that of steel reinforcement. The concrete reinforcing bar according to this embodiment has high alkali resistance, high strength, is easy to process with secondary methods such as bending, and is lighter than steel reinforcement. Furthermore, the concrete reinforcing bar according to this embodiment can be manufactured at low cost.

[0029] The present invention will be described in more detail below with reference to examples, but these examples do not limit the present invention in any way. [Examples]

[0030] (Manufacturing of FRP strand rods) FRP rods were manufactured using a pultrusion forming machine manufactured by Kobe Steel, Ltd. The manufacturing process is as described above with reference to Figures 3-5. Five FRP strand rods (Examples 1-3, Comparative Examples 1 and 2) were prototyped using basalt fiber (BF) as the reinforcing fiber. For the matrix, a few percent of a compatibilizer was added to highly fluid polypropylene (PP). BF with a fiber diameter of 17 μm and fineness of 4800 tex was used. The molded FRP rods were internally observed using X-ray CT (ZEOSS), and non-circularity and V were observed. f The following was calculated. In addition, a tensile test was performed using a universal testing machine (manufactured by Shimadzu Corporation), and the load retention rate was calculated by dividing the tensile breaking load after alkaline immersion by the tensile breaking load before alkaline immersion and multiplying by 100.

[0031] The alkali resistance of FRP rods was evaluated in accordance with JIS A1193. An alkaline solution simulating the pore solution of concrete was adjusted to 60°C and pH 12.5-13.0, and the FRP rods were immersed in a constant temperature bath for 28 days. After that, the load was measured by tensile testing. The measurement results were categorized as "Excellent" (load retention rate of 95% or more), "Good" (load retention rate of 90-94%), and "Poor" (load retention rate of 95% or more). 89 The performance was evaluated in three stages (below %). In addition, handling performance was evaluated in three stages: "Excellent" (no fibers get stuck in the hand and no protrusions), "Good" (no fibers get stuck in the hand, but fine, broken fibers are visible), and "Poor" (fibers get stuck in the hand).

[0032] Figure 6 shows X-ray CT images of Examples 1 and 2 and Comparative Examples 1 and 2. Example 1 is an FRP rod manufactured with three rovings and a die of Φ4.8 mm. Example 2 is an FRP rod manufactured with three rovings and a die of Φ5.0 mm. Comparative Example 1 is an FRP rod manufactured with four rovings and a die of Φ4.8 mm. Comparative Example 2 is an FRP rod manufactured with four rovings and a die of Φ5.0 mm. From Figure 6, it can be seen that a coating layer of PP resin is reliably formed in Examples 1 and 2.

[0033] Table 1 shows the characteristics of the FRP rods of Examples 1-3 and Comparative Examples 1 and 2. Here, Example 3 is an FRP rod manufactured with four rovings and a die of Φ5.0 mm. [Table 1]

[0034] Table 1 shows that the thickness of the coating layer is 85 μm or more, and the V of the core material f The FRP rods of Examples 1 and 2, which have a composition of 60% or more, are found to have superior strength, alkali resistance, and handling compared to Comparative Examples 1 and 2.

[0035] Next, the following samples were prototyped. The twist angle (measured at 3 points for each distance, and the measured values of the 3 points were averaged) was calculated from X-ray CT (manufactured by ZEOSS) of the prototyped FRP rod. ·Example 4 Fiber: Glass fiber (GF) Core material V f (Calculated by image analysis using X-ray CT) 80.2%, roller angle 2θ (during molding) 10 degrees ·Example 5 Fiber: GF Core material V f (Calculated by image analysis using X-ray CT) 63.9%, roller angle 2θ (during molding) 30 degrees ·Example 6 Fiber: GF Core material V f (Calculated by image analysis using X-ray CT) 82.5%, roller angle 2θ (during molding) 60 degrees ·Example 7 Fiber: Basalt fiber (BF) Core material V f (Calculated by image analysis using X-ray CT) 80.5%, roller angle 2θ (during molding) 30 degrees ·Example 8 Fiber: BF Core material V f (Calculated by image analysis using X-ray CT) 61.5%, roller twist angle 2θ (during molding) 30 degrees

[0036] The twist angles of Examples 4 to 8 are as follows. ·Example 4: 0.87 to 3.82 degrees (distances from the center: 0.25, 0.5, 0.75, 1.0 mm) ·Example 5: 1.59 to 5.61 degrees (distances from the center: 0.25, 0.5, 0.75 mm) ·Example 6: 3.38 to 14.27 degrees (distances from the center: 0.25, 0.5, 0.75 mm) ·Example 7: 1.9 to 10.46 degrees (distances from the center: 0.5, 1.0, 1.5 mm) ·Example 8: 3.11 to 14.78 degrees (distances from the center: 0.5, 1.0, 2.0, 2.5 mm) The relationship between the twist angle of Examples 4 to 8 and the distance from the center of the core material is shown in Figure 7. From Figure 7, it is found that the twist angle is proportional to the distance from the center of the core material.

[0037] We created FRP rods (made of basalt fiber and polypropylene, hereinafter also referred to as BFPP) with increased diameter through bundling and twisting. The BFPP ropes were twisted with the cooperation of Komatsu Matere Co., Ltd. Figure 8 shows photographs of BFPP bent at 90 degrees and 180 degrees. We confirmed that the bending process could be easily performed using hot air from a heat gun. [Industrial applicability]

[0038] The concrete reinforcement composite material of the present invention can be used as concrete reinforcing bars. [Explanation of symbols]

[0039] 10. Composite material for concrete reinforcement, 12. Core material, 14. Covering layer.

Claims

1. A core material formed from a bundle of reinforcing fibers, It consists of a thermoplastic resin coating layer covering the core material, The thermoplastic resin of the coating layer is impregnated into the core material, the thickness of the coating layer is 85 μm or more, and the fiber volume content of the core material is V f A composite material for concrete reinforcement characterized by having 60% or more of [a certain component].

2. The concrete reinforcement composite material according to claim 1, characterized in that the non-circularity of the concrete reinforcement composite material is 1 to 5%, and the non-circularity of the core material is 1 to 6%.

3. The concrete reinforcing composite material according to claim 1 or 2, characterized in that the twist angle of the reinforcing fibers is 0.87 to 15°.

4. The concrete reinforcing composite material according to any one of claims 1 to 3, characterized in that the twist angle of the fibers measured in the longitudinal cross-section of the reinforcing fibers is proportional to the distance from the center of the core material to the position of the fibers.

5. The concrete reinforcing composite material according to any one of claims 1 to 4, characterized in that the thermoplastic resin is a polyolefin resin.

6. The concrete reinforcing composite material according to any one of claims 1 to 5, characterized in that the reinforcing fiber is at least one selected from the group consisting of glass fiber, basalt fiber, carbon fiber, and aramid fiber.

7. A concrete reinforcing bar characterized by comprising a concrete reinforcing composite material according to any one of claims 1 to 6.

8. A method for manufacturing a concrete reinforcing composite material comprising a core material formed from a fiber bundle of reinforcing fibers and a coating layer of thermoplastic resin covering the core material, A method for manufacturing a composite material for concrete reinforcement, characterized by including a pultrusion molding step in which the core material is guided into an impregnation head filled with molten thermoplastic resin, the core material is impregnated with the molten thermoplastic resin to form the core material as a resin-impregnated fiber bundle, and the core material is twisted inside the impregnation head before being pulled out of the impregnation head and shaped.

Citation Information

Patent Citations

  • Reinforced fiber reinforced bar, reinforcing method for concrete structure, and manufacture of reinforced fiber reinforced bar

    JP1999070596A

  • Reinforced fiber reinforcing bar and reinforcing method for concrete structure

    JP1999124957A

  • Method for producing long fiber-reinforced thermoplastic resin pellet

    JP2011062971A

  • String-like reinforcement fiber composite

    JP2012251378A